Kadar Vitamin C Jeruk Sunkist Peras dan Infused Water - Haitami Haitami; Annisa Ulfa; Akhmad Muntaha (Medical Laboratory Technology Journal, 2017)
Orange is one of the fruits that are widely consumed by the society, besides to the sweet taste and attractive appearance orange also has various benefits for the body such as vitamins and minerals. The famous and much-favored orange is a beneficial Sunkist orange can treat fever, treat infections, improve body immunity and decreasing the number of cholesterol. There are several ways of processing oranges such as orange juice and infused the water. The purpose of this study is to know the ratio of vitamin C content in the juice of Sunkist with infused water orange Sunkist. Types of research is analytic survey with comparative study approach. The research sample used was orange Sunkist which made two treatment that is the juice of Sunkist orange and infused water by using Iodimetry titration method. The results of the average vitamin C content in 10 samples of citrus Sunkist for 348,82 ppm and the average vitamin C level in 10 samples infused water of orange Sunkist equal to 67,59 ppm. Based on statistical test result using Independent Sample T-Test test stated that there is the difference of vitamin C content on freshly squeezed orange Sunkist with infused water of orange Sunkist with the value of significance 0.000. Suggested for further researcher can do research of vitamin C Infused water level by combining with other fruit